1991
DOI: 10.1126/science.2028254
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Behavior and Health in Consanguineous Marriages

Abstract: In many regions of Asia and Africa, consanguineous marriages currently account for approximately 20 to 50% of all unions, and preliminary observations indicate that migrants from these areas continue to contract marriages with close relatives when resident in North America and Western Europe. Consanguinity is associated with increased gross fertility, due at least in part to younger maternal age at first livebirth. Morbidity and mortality also may be elevated, resulting in comparable numbers of surviving offsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
226
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 299 publications
(236 citation statements)
references
References 70 publications
8
226
2
Order By: Relevance
“…In the general population, the risk of abnormality or death in early childhood is about 2% to 2.5% for nonconsanguineous couples compared with 5% for consanguineous couples. It has been suggested by Bittles et al (1991) that most of this increase occurs in a sub-set of consanguineous families that happen to harbour recessive mutations, suggesting that identification of these high-risk families would provide an opportunity to provide targeted genetic services. Autosomal recessive disorders vary in severity, but many lead to early death or chronic disability and therefore they impose a significant health and economic burden on families and health care services.…”
Section: Introductionmentioning
confidence: 99%
“…In the general population, the risk of abnormality or death in early childhood is about 2% to 2.5% for nonconsanguineous couples compared with 5% for consanguineous couples. It has been suggested by Bittles et al (1991) that most of this increase occurs in a sub-set of consanguineous families that happen to harbour recessive mutations, suggesting that identification of these high-risk families would provide an opportunity to provide targeted genetic services. Autosomal recessive disorders vary in severity, but many lead to early death or chronic disability and therefore they impose a significant health and economic burden on families and health care services.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to common opinion, consanguinity is not confined to Muslim communities. Many other religious groups, including the Lebanese, Jordanian and Palestinian Christian populations, also practise consanguineous between uncles and their nieces (F = 0.0125) 16 .…”
Section: Consanguinity and Social Structurementioning
confidence: 99%
“…This result suggests some variation in the proportion of consanguinity in this Pakistani sample. The majority of Pakistani immigrants trace their origins to rural Mirpur and, as other studies have observed (Rao & Inbaraj, 1977;Bittles, et al 1991;Bittles, 1994), the highest rates of consanguinity are to be found in rural communities. It appears that this trend has continued in their immigrant descendants.…”
Section: Discussionmentioning
confidence: 65%
“…Marriage within Pakistani Muslim societies, however, has fewer exclusions: first order relatives; parents, sibs and parent's sibs (Ballard, 1990). Amongst Punjabi Muslims, an active preference for first cousin marriage is also common (Bittles et al 1991) and there is evidence that such arrangements are increasing in prevalence (Darr & Modell, 1988). One other important aspect of Pakistani Muslim societies is the extent of family networks that develop through biradheri endogamy, where marriages within these large kin-networks often occur between related individuals (Darr & Modell, 1988;Ballard, 1990).…”
Section: Discussionmentioning
confidence: 99%